Purification and characterization of TFIIIA from Acanthamoeba castellanii - Polakowski, Nicholas, author; Paule, Marvin R., advisor (Colorado State University. Libraries, 2001)
Our interest has been in studying the mechanisms of RNA polymerase III (Pol III) transcription and the regulation of this process in A. castellanii, which was specifically focused on TFIIIA. This factor only activates Pol Ill-mediated transcription from 5S RNA genes and is the first of three general Pol Ill-specific transcription factors that is assembled onto the DNA to form the preinitiation complex. Previous work in our laboratory has shown that A. castellanii TFIIIA is under direct regulatory control. During the process of A. castellanii encystment, both ribosomal RNA (rRNA) and 5S RNA transcription are coordinated down-regulated. The loss of 5S RNA synthesis is associated with the disappearance of TFIIIA activity, and the loss of rRNA synthesis is caused by a modification of polymerase I or a tightly associated factor that is reversible. Based on the mechanism of Pol I regulation, we suspect that TFIIIA is regulated in a similar fashion. Our primary objective was, therefore, to determine if TFIIIA remained present in cysts by using antibodies. Because TFIIIA is not evolutionarily conserved in its primary sequence, antibodies raised against other homologues of this factor have shown little or no cross reactivity with A. castellanii TFIIIA. We have, therefore, purified this protein as the preliminary step in elucidating its regulatory control. This factor was found to have a size of 59 kDa, which is significantly larger than all other known TFIIIA homologues. It was also found to bind to and footprint the DNA promoter in a manner more similar to TFIIIA from vertebrates. To compare the mechanisms that regulate Pol Ill-mediated transcription in different organisms, we have also examined Pol Ill-mediated transcriptional regulation in yeast. During stationary phase, Pol III transcription is down-regulated, but the mechanisms involved in the process are not well understood. In studying tRNA synthesis, we have found that in vivo observations diverge from what is seen in vitro. Specifically, Pol Ill-mediated transcriptional repression is much more severe in vivo. This illustrates that transcriptional regulation cannot be completely recapitulated from yeast whole-cell extracts. However, we did identify an inhibitor that specifically decreases the ability of extracts to support Pol Ill-mediated transcription. The action of this inhibitor may complement other mechanisms involved in down-regulating Pol Ill-mediated transcription.
Missing page 60.
Keywords: molecular biology